APPLICATION OF LEARNING CYCLE MODEL (5E) LEARNING WITH CHART VARIATION TOWARDSTUDENTS’ CREATIVITY (Jurnal Pendidikan IPA Indonesia, 2015)
This study aims to determine the differences in the application of the model LC (5E) with a technique variation (interrelationship diagram / ID and affinity diagrams / AD) of two classes of different school (XIPA-8 class of SMAN 3 Surakarta and class XIPA-6 of SMAN 3 Boyolali), toward the increase of students’ creativity. This research is a qualitative descriptive study. The results of this study, we can conclude that the application of the model LC (5E) with a technique variation at two schools can improve students' creativity despite different levels of improvement.